ITER beam aided diagnostics. (1st February 2022) - Levinton, F.M.; Reichert, H.; De Bock, M.
Abstract: We provide an overview of ITER beam aided diagnostics, including the motional Stark effect (MSE) and charge exchange recombination spectroscopy (CXRS). ITER presents several unique challenges to plasma diagnostics in general and beam-aided diagnostics in particular. The large size, long pulse, and DT operation drives much of the diagnostic design. This in turn has driven a significant R&D effort concerning the maintenance of plasma facing mirrors with sufficient reflectivity to maintain the utility of the diagnostic. In the case of MSE a new approach utilizing spectral splitting will be pursued instead of the conventional polarimetry approach due to the difficulty of maintaining and calibrating the polarizations properties of the plasma facing mirror.